2006
DOI: 10.1038/sj.tpj.6500423
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced agranulocytosis in schizophrenic Caucasians: confirming clues for associations with human leukocyte class I and II antigens

Abstract: Clozapine-induced agranulocytosis (CA) is still among the least understood adverse drug reactions in psychopharmacology. In particular, its genetic background is far from being clarified. Within the framework of a casecontrol study, we performed human leukocyte antigen (HLA) genotyping and haplotype analyses in 42 non-Jewish Caucasian schizophrenic patients (N ¼ 42) suffering from CA and 75 non-Jewish Caucasian schizophrenic patients treated with clozapine without developing CA. While controlling for age (Po0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 32 publications
0
31
1
Order By: Relevance
“…For HLA class II alleles, HLA-DQB-0502, -DRB1-0101, and -DRB3-0202 were found to be associated with CIA, but in contrast to previous findings, no significant association was found between CIA and the HLA-B38 allele [63]. More recently, Dettling et al [64] identified a significant association with CIA for two Cw-7-related two-locus haplotypes with HLA-Cw7-B18 and HLACw7-B39; one HLA class II two-locus haplotype with HLA-DRB5-0201-DRB4; and a three-locus haplotype with HLACw7drb5, HLA-Cw7-B39-DRB5, and HLA-Cw7-B44-DRB5. The authors concluded that combinations and possibly epistasis of alleles or haplotypes at several HLA class I loci, spanning from MHC-I over MHC-III to MHC-II, may be [65].…”
Section: Overview Of Genetics Of Clozapine-induced Agranulocytosis (Mmentioning
confidence: 73%
See 1 more Smart Citation
“…For HLA class II alleles, HLA-DQB-0502, -DRB1-0101, and -DRB3-0202 were found to be associated with CIA, but in contrast to previous findings, no significant association was found between CIA and the HLA-B38 allele [63]. More recently, Dettling et al [64] identified a significant association with CIA for two Cw-7-related two-locus haplotypes with HLA-Cw7-B18 and HLACw7-B39; one HLA class II two-locus haplotype with HLA-DRB5-0201-DRB4; and a three-locus haplotype with HLACw7drb5, HLA-Cw7-B39-DRB5, and HLA-Cw7-B44-DRB5. The authors concluded that combinations and possibly epistasis of alleles or haplotypes at several HLA class I loci, spanning from MHC-I over MHC-III to MHC-II, may be [65].…”
Section: Overview Of Genetics Of Clozapine-induced Agranulocytosis (Mmentioning
confidence: 73%
“…Loci highlighted as significant in the GWAS included HLA-DQB1, granulocyte-colony stimulating factor receptor (G-CSFR), and dopamine receptor D1. The investigators also found that a variant in HLA-DQB1, 6672G>C, was associated with risk of CIA, reporting a 16.9 times increased risk for carriers of this marker [64]. A commercial test was marketed in 2007 based on data from 136 patients in the cohorts utilizing the HLA-DQB1 6672G>C genotype to classify patients as "lower risk" or "higher risk" for CIA.…”
Section: Overview Of Genetics Of Clozapine-induced Agranulocytosis (Mmentioning
confidence: 99%
“…African Caribbeans were also more likely to have a diminished baseline WBC count and neutrophil count when compared with White counterparts. Dettling et al (2007) focused on specific genetics during their research on 42 non-Jewish Whites. Human leukocyte class 1 and class 2 antigens were found to have a link with clozapine-induced blood dyscrasias.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Haplotypes in HLA-DQB1, HLA-C, NTSR1, DRD1 and CSF2RB were significant with a permutation test adjusted P < 0.05. Methods: We attempted to replicate the findings from four of these genes in an independently collected cohort of 49 cases and 78 controls (Mosyagin et al, 2005;Dettling et al, 2006). Cases were patients with an ANC < 500 during clozapine treatment and controls were treated with clozapine for at least 2 years without an adverse effect on the WBC or ANC.…”
Section: P 088 High Frequency Of Cyp2d6 Pms In the Faroe Islands A Rimentioning
confidence: 99%